Piezoelectric Energy Harvesting Technology: From Materials, Structures, to Applications. Issue 3 (6th January 2022) - Li, Tao; Lee, Pooi See
Abstract : The piezoelectric energy harvesting is a promising, interesting and complex technology. Herein, the aim is to review the key groups of parameters that contribute to the performance of energy harvesting and to offer a guideline for the future development. For this purpose, a universal theoretical model is developed. According to the model, the parameters are divided into six groups. Each group is then discussed. First, a discussion on the piezoelectric materials status, advantages and disadvantages of ceramics, polymers, single crystals, composites, nanomaterials, and lead‐free materials are summarized. The orientation of materials is also discussed. Second, the structure designs, including off‐resonance, on‐resonance, and impact design were introduced. Third, typical sources of excitations and vibrations are given, including direct contact force, low vibration force, hydraulic, pneumatic power, and acoustic power. The fourth consideration is on the effect of frequency and speed is discussed, focusing on the high‐frequency and high‐speed conditions. This is followed by the effect of electrical load on the output power of an energy harvester was discussed. Last, the parameters of energy accumulation effect and methods are also introduced. Following the above discussion, some examples are provided to show the potential applications, including the areas of structural health monitoring, vibration engines, pavement road energy harvesting, wireless sensor nodes, and human gait power. Finally, at the end of the review, the future challenges are addressed. Abstract : The important parameters which affect the performance of a piezoelectric energy harvester are identified herein. The materials, structural design, frequency/speed, excitations, external load, time effect, and typical applications are summarized and discussed.